The Phytochemical Characterization of a Cili (Rosa roxburghii) Fruit Low-Temperature Extract with Hepatoprotective Effects - Rifeng He; Ziling Lian; Zhongjun Cheng; Yang Liu; Xiaoyan Peng; Yong Wang; Hang Ma; Xue Zhou; Fahuan Ge (Foods)
Cili (Rosa roxburghii Tratt) fruit is a nutrient-rich edible plant known for its antioxidant and hepatoprotective properties. However, conventional extraction methods often lead to the degradation of its bioactive compounds. In this study, we developed a low-temperature homogenate-assisted high-pressure disruption extraction (HHPD) method to obtain a phytochemically enriched cili fruit extract (HHPD-CFE). The chemical characterization of the HHPD-CFE showed that it contained higher levels of polyphenols, polysaccharides, and superoxide dismutase (SOD) than those in conventional squeeze extraction. The hepatoprotective effects of the HHPD-CFE were evaluated in oxidative stress-induced liver injury and hepatic fibrosis models. The HHPD-CFE mitigated oxidative damage by reducing malondialdehyde while enhancing SOD and glutathione activity. Additionally, the HHPD-CFE inhibited the activation of hepatic stellate cells (HSC-T6) and reduced collagen deposition, suggesting a protective role against liver fibrosis. These findings support that the HHPD-CFE is a promising botanical extract with enriched bioactive compounds and liver-protective properties. This study supports the potential application of optimized extraction techniques to preserve thermosensitive compounds and improve the efficacy of functional foods for liver health.